2017
DOI: 10.1016/j.carbpol.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and immunomodulatory activity of a water soluble polysaccharide isolated from Botrychium ternatum

Abstract: As a folk medicine, Botrychium ternatum has been used for thousands of years in China. In the present work, a water soluble polysaccharide BTp1 was extracted and purified from B. ternatum. Based on the MALDI matrix 3-aminoquinoline-α-cyano-4-hydroxycinnamic acid, the molecular weight of BTp1 was determined to be 11638Da directly. Monosaccharide analysis showed that BTp1 was composed of arabinose (Ara). Combining enzymatic hydrolysis and subsequent MALDI-TOF analysis, a linear backbone of BTp1, consisted of (1→… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…GLP from the sporodumbroken spores of G. lucidum was extracted by hot water extraction method as described before 11 . Briefly, 5 g power of sporodum-broken spores of G. lucidum was placed in 100 ml of ultrapure water, lipid was first removed as described before 76 and then oscillated (300 rpm) at 70 ℃ for 12 h. However, the proportion of residual lipid and protein contents were not determined at present. The solution was centrifuged at 4000 rpm for 15 min to remove insoluble materials, and further purified to remove protein using Sevage method as described before 76 , and centrifuged again to collect the supernatant.…”
Section: Preparation Of Glpmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP from the sporodumbroken spores of G. lucidum was extracted by hot water extraction method as described before 11 . Briefly, 5 g power of sporodum-broken spores of G. lucidum was placed in 100 ml of ultrapure water, lipid was first removed as described before 76 and then oscillated (300 rpm) at 70 ℃ for 12 h. However, the proportion of residual lipid and protein contents were not determined at present. The solution was centrifuged at 4000 rpm for 15 min to remove insoluble materials, and further purified to remove protein using Sevage method as described before 76 , and centrifuged again to collect the supernatant.…”
Section: Preparation Of Glpmentioning
confidence: 99%
“…Briefly, 5 g power of sporodum-broken spores of G. lucidum was placed in 100 ml of ultrapure water, lipid was first removed as described before 76 and then oscillated (300 rpm) at 70 ℃ for 12 h. However, the proportion of residual lipid and protein contents were not determined at present. The solution was centrifuged at 4000 rpm for 15 min to remove insoluble materials, and further purified to remove protein using Sevage method as described before 76 , and centrifuged again to collect the supernatant. The supernatant was then concentrated and freeze-dried using H051 freeze dryer (LaboGene, Lynge, Denmark) to obtain GLP for subsequent experiments.…”
Section: Preparation Of Glpmentioning
confidence: 99%
“…The activities of plant polysaccharides include immune regulation, anti-tumor, anti-radiation, and anti-viral effects (21, 2527), and the structures of polysaccharides are directly related to their functional activities (28). Kralovec et al reported that a polysaccharide/glycoprotein complex with a molecular weight >100 kDa and consisting mainly of galactose, rhamnose, and arabinose has high biological activity (29).…”
Section: Introductionmentioning
confidence: 99%
“…The purities and Mwt of dextrans were determined by high‐performance gel permeation chromatography (Supporting Information Figure S5). Extraction of polysaccharides form C. morifolium, B. ternatum , and L. barbarum were carried out according to a previous method with some modifications . In brief, dried sample was ground into a fine powder and then boiled with deionized water for 3 h, followed by filtration.…”
Section: Methodsmentioning
confidence: 99%